Microstructural and Fractographical Studies on Quenched and Tempered Armor Steels - (:unkn) unknown (CARL HANSER VERLAG, 2010)
In this study, a boron-alloyed experimental steel has been rolled to form a sheet product, and an austenization treatment has been performed, followed by rapid quenching and then tempering. By austenization, a homogeneous austenite phase is obtained and a martensitic microstructure is formed after rapid quenching. This kind of microstructure exhibits high hardness, but low toughness. Thus, a tempering heat treatment is applied at a proper temperature (200 degrees C and 600 degrees C) and various times, in order to provide optimum toughness and to develop an ideal combination of strength and toughness. After this process, at first the phases formed during the equilibrium state have been studied for the alloy system using ThermoCalc data, and also their amounts have been evaluated. The microstructures acquired after the heat treatments have been examined by light microscopy. The effects of the formed microstructures on mechanical properties are comparatively given by their strength, toughness, and elongation values. Furthermore, the failure mechanism with fractografical examinations has been determined by using a Scanning Electron Microscope (SEM).
Keywords: HIGH-SPEED STEELS